Precarious work as predictor of moral harassment in the Brazilian Unified Social Assistance System (USAS) - Fonseca, Rozana Maria da; Nunes, Sandra Adriana Neves; Carrusca Vieira, Carlos Eduardo (Cuadernos de Trabajo Social, 2025)
In the logic of neoliberal managerialism, the intensification of work, the cult of performance, and the pursuit of productivity and profit at the expense of labor rights and workers’ health exacerbate abusive management practices such as moral harassment. This study investigated whether different dimensions of precarious work would predict moral harassment in a sample of 747 SUAS workers, with a mean age of 38.34 years (SD = 8.22) and predominantly female (88.6%). A sociodemographic questionnaire was used, along with the Moral Harassment Workplace Scale (MHWS) and the Perception Scale of Work Conditions Quality and Employment Bond (PSWCQEB). “Quality of Employment Bond,” “Quality of Interprofessional Relations and Workplace Equality” and “Precarious Work” were significant predictors of this type of harassment, explaining 35% of variance in moral harassment due to labor conditions. “Quality of Interprofessional Relations and Workplace Equality” and “Healthy and Safe Work Environment” explained 13% of variance in moral harassment due to prejudice. “Quality of Interprofessional Relations and Workplace Equality” was negatively associated with moral harassment in situations involving humiliation, explaining 32.3% of variance. The study concludes that moral harassment and precarious work are interconnected phenomena that impact SUAS workers and reflect the logics of capitalist social relations of production and neoliberalism, even in the context of public management.Keywords: Moral harassment; precarious work, Unified Social Assistance System; multiple regression analysis; workers.
Keywords: moral harassment; work precariousness; unified social assistance system; multiple regression analysis; workers